2008
DOI: 10.1007/s10152-008-0128-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation in early developmental stages in two populations of an intertidal crab, Neohelice (Chasmagnathus) granulata

Abstract: Duration of embryonic development, egg size, larval size at hatching, and starvation tolerance of the first zoeal stage were studied in an intertidal crab from the southwestern Atlantic, Neohelice (formerly Chasmagnathus) granulata. These reproductive traits were quantified comparing (a) two populations living in ecologically contrasting coastal habitats in Argentina, a brackish lagoon, Mar Chiquita, MC vs. an open marine habitat near San Antonio, Patagonia, SA, (b) beginning vs. end of the reproductive season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 16 publications
5
30
0
Order By: Relevance
“…700 km in straight line from the studied sites. These data were reported by Bas et al (2005Bas et al ( , 2007Bas et al ( , 2008Bas et al ( , 2014 (1994,1996,2012).…”
supporting
confidence: 73%
“…700 km in straight line from the studied sites. These data were reported by Bas et al (2005Bas et al ( , 2007Bas et al ( , 2008Bas et al ( , 2014 (1994,1996,2012).…”
supporting
confidence: 73%
“…Ituarte et al (2006) demonstrated that the late start and short duration of the reproductive season at SAO (compared to MCL), was due to females not fully developing their ovaries during winter, probably caused by a limited food supply. Further, other studies showed that the duration of the embryonic development was similar in both study areas (Bas et al 2008). Consequently, females from SAO become receptive fewer times (about half) in a single season since the reproductive season was considerably shorter than at MCL.…”
Section: Discussionmentioning
confidence: 59%
“…Burrows can reach high densities, with up to 60 burrows m -2 (Iribarne et al 1997). Previous studies of N. granulata have compared two populations inhabiting contrasting habitats: Mar Chiquita lagoon (MCL), an oligo-polyhaline estuary located in Buenos Aires Province, Argentina (37°45 0 S; 57°19 0 W), and San Antonio Oeste (SAO) bay, an eu-hyperhaline habitat located in Río Negro Province, Argentina (40°46 0 S; 64°50 0 W), where differences related to the population structure (Bas et al 2005), reproductive biology (Ituarte et al 2006), number, size and composition of eggs and embryonic development (Bas et al 2007(Bas et al , 2008 were found to be linked to the type of habitat and the environmental conditions. Those studies demonstrated that the reproductive season is longer in MCL than in SAO, extending from September to February and from November to January, respectively, although the differences in the reproductive traits were not associated with a latitudinal temperature gradient; instead, the quality and quantity of benthic food resources and productivity may be responsible for the observed reproductive differences (Ituarte et al 2006;Bas et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The production of eggs with different characteristics along the reproductive cycle has been documented in other crustacean species (see Díaz 1980;O'Leary Amsler and George 1984;Paschke et al 2004;Bas et al 2007Bas et al , 2008Urzúa et al 2012;Bell and Fish 1996), but factors responsible for such developmental plasticity are, in most cases, matter of speculation. Differences observed in P. macrodactylus females might be simply the result of varied resource investment performed by individuals of different age or size.…”
Section: Discussionmentioning
confidence: 99%